ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ansyarif Khalid; Ismail Badollahi; Ramliady Ramliady (INVOICE : JURNAL ILMU AKUNTANSI, 2019)
Analysis of Financial performance of manufacturing companies listed on the Indonesia stock exchange, Thesis Faculty of Economics and business Department of Accounting University of Muhammadiyah Makassar. Guided by Mentors I h. Ansyarif Khalid and Supervisor II Ismail Badollahi. This research aims to know the financial performance of the manufacturing companies listed on the Indonesia stock exchange Period 2014-2016. The type of research used in the study is the analysis of quantitative data.  The collection of data using secondary data obtained from the audited financial statements. Population and sampelnya is taken on the basis of certain criteria or purposive Sampling. Research results can be concluded that if seen from the Liquidity ratio and the solvabilitasnya PT Kalbe Farma Tbk is the best. If seen from the profitability ratio of PT Unilever Indonesia Tbk is the promise in generating profits.